2021
DOI: 10.1093/jas/skab320
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxy-selenomethionine as an organic source of selenium in the diet improves boar reproductive performance in artificial insemination programs

Abstract: This study aimed to compare different selenium (Se) sources in the diet on boar's semen quality and fertility. For this, 28 boars aged 8 to 28 months were fed with the following dietary treatments for 95 days: 0.3 mg Se/kg as sodium selenite (SS, n = 14) and 0.3 mg Se/kg as hydroxy-selenomethionine (OH-SeMet, n = 14). During this period, two experiments were carried out. In experiment 1, the semen of all boars was evaluated every 2 weeks. Raw semen was initially evaluated for the processing of seminal doses, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 51 publications
0
2
1
Order By: Relevance
“…The findings of the current study are not fully supported by the results of the previous research of Petrujkić et al who found an increased GPx activity in boar seminal plasma after 90 days of supplementation at the dose of 0.3 mg/kg of sodium selenite [25]. In contrast, Pavaneli et al did not observe the effects of dietary Se treatments at the same doses on GPx activity in seminal plasma [26].…”
Section: Discussioncontrasting
confidence: 99%
“…The findings of the current study are not fully supported by the results of the previous research of Petrujkić et al who found an increased GPx activity in boar seminal plasma after 90 days of supplementation at the dose of 0.3 mg/kg of sodium selenite [25]. In contrast, Pavaneli et al did not observe the effects of dietary Se treatments at the same doses on GPx activity in seminal plasma [26].…”
Section: Discussioncontrasting
confidence: 99%
“…Selenium (Se) is recognized for its potent antioxidant activity and potential to enhance male mammalian fertility. 29 Previous animal studies have shown that Se supplement can improve the semen quality of mammals 30 and poultry 31 or alleviate stress-induced adverse effects on the semen quality. 32 Consistent with these findings, our study found that SeGlu supplementation for 30 days in rats improved the sperm motility and survival rate, with a significant improvement observed in the 0.15 mg Se per L group ( p < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, studies have shown that broiler breeders’ diets containing organic compounds high in Se may have positive effects on offspering during the rearing period (Zhang et al., 2014 ). Recently, a new source of stable organic selenium, which is a hydroxy analogue of selenomethionine, has been created and is used instead os selnomethionine, which is unstable and easily oxidized in each pure form (Pavaneli et al, 2021 ). The higher bioavailability of seleno‐amino acid composition compared to other organic or inorganic forms has been confirmed previously by Couloigner et al.…”
Section: Introductionmentioning
confidence: 99%